Pembelajaran Aktif dan Diferensiatif melalui Lapbook, Kuis Interaktif, dan Flipbook - Hafizah, Hafizah; Pebriana, Putri Hana (TSAQOFAH, 2025)
The Teacher Professional Education Program (Program Pendidikan Profesi Guru/PPG) serves as a strategic platform for cultivating teacher professionalism through the intensive integration of educational theory and field practice. This article presents an in-depth reflection on the experience of participating in the PPG, with a focus on the application of active and differentiated learning strategies through the use of lapbook media, interactive quizzes, and flipbook. Employing a reflective-narrative method, the article illustrates the participant’s transformation from the stage of self-identification as a prospective educator to the implementation of instructional practices in the classroom. The findings show that the applied learning strategies effectively enhanced student engagement, accommodated diverse learning styles, and contributed to character development. Furthermore, the use of interactive media supported a more meaningful and adaptive learning process tailored to student needs. This article underscores the importance of formative assessment, context-based use of technology, and the strengthening of pedagogical competencies as essential components in efforts to improve the quality of national education through the PPG. This reflective contribution is expected to enrich the discourse on best practices in the development of teacher professionalism and instructional innovation at the primary and secondary school levels.